The Impact of Corporate Governance towards Capital Structure and Corporate Performance in Banking Industry - Dewi Mandiri, Satimah Sarisitamah; Rahayu, Sri Mangesti; Nuzula, Nila Firdausi (Profit: Jurnal Adminsitrasi Bisnis, 2023)
Bank is important because of its role and duties. Liquidity risk is attached to banking industry, forcing banks to comply with the policies implemented by the government, especially complying with the implementation of corporate governance in their operations. This study aims to analyze effect of Corporate Governance (Board Size and Board of Meetings) on Capital Structure (Debt to Equity Ratio and Capital Adequacy Ratio) and Corporate Performance (Return on Assets, Return on Equity, and Non Performing Loans) in all a profit-generating banking company listed on the Indonesia Stock Exchange (IDX) during the 2015-2019 period. The number of samples used in this study were 23 companies. The analysis in this study is descriptive analysis and Partial Least Square (PLS), using secondary data.